Analisis Persiapan Masuk Perguruan Tinggi Negeri Pada Masyarakat Desa Lebo Kabupaten Barito Timur - Fendy Hariatama; Rinto Alexandro; Liling Lenlioni; Tonich Uda; Hendrowanto Nibel (Edunomics Journal, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process for students actively to develop their potential so that they have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves and society. Higher education is a problem that occurs in Indonesia related to efforts to educate the nation's life and shape Indonesian human resources as a whole. As stated in Article 31 paragraph (1) of the 1945 Constitution, every citizen has the right to education. (2) Every citizen is obliged to attend basic education and the government is obliged to pay for it. However, due to the lack of information about education, many people pay less attention to their children's education. This is also the reason why teenagers in Lebo Village, Pematang Karau District, East Barito Regency, on average, only finish high school. So that the purpose of the presence of the research team is to provide a qualitative analysis of the preparation for entering college in the Lebo Village community so that it can become an important reference for changing people's mindsets about the importance of education. Because as it is known that people who receive education at the tertiary level are one of the important things in order to be able to provide ideas and ideas for the progress of the village. The results of the study show that in Lebo Village there are only elementary schools, for middle and high schools there are still no. The village is located in a location that is difficult to signal, so it is difficult for the community to access information. On average, after graduating from high school, parents are more likely to direct their children to work than to continue their education to college. There has been no visit or socialization from the government regarding the preparations that must be made to continue education to the tertiary level.